Digital Editing and Montage: The Vanishing Celluloid and Beyond - Lefebvre, Martin; Furstenau, Marc (Cinémas / Revue d’études cinématographiques)

(untitled) (Cinémas, 2002)
AbstractIn this essay we consider some of the effects of digital film editing technology on editing. Through an analysis of this technology, as well as DVD technology, we examine the impact these new interfaces have on the film experience. In addition, a study of the effects of compositing—understood here as digital montage par excellence—permits us to dig deeper into its impact on traditional approaches to film style, as well as to question the anxiety stemming from the new technology, given that many critics today argue that digitization has obliterated film’s indexicality.